2017
DOI: 10.1186/s13756-017-0228-6
|View full text |Cite
|
Sign up to set email alerts
|

No nosocomial transmission under standard hygiene precautions in short term contact patients in case of an unexpected ESBL or Q&A E. coli positive patient: a one-year prospective cohort study within three regional hospitals

Abstract: BackgroundMany Highly Resistant Gram Negative Rod (HR-GNR) positive patients are found unexpectedly in clinical cultures, besides patients who are screened and isolated based on risk factors. As unexpected HR-GNR positive patients are isolated after detection, transmission to contact patients possibly occurred. The added value of routine contact tracing in such situations within hospitals with standard hygiene precautions is unknown.MethodsIn 2014, this study was performed as a prospective cohort study. Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…32 Published literature indicates that outside of outbreaks, only a fraction of ESBL-E identified on wards is transmitted between patients. 24,28,33 Similar results for prevalence on admission and new acquisitions indicate no systematic differences between the intervention periods. Patients readmitted to the wards might have had complex courses of treatment, and thus selection could have had a large role in this group of patients, but the results of sensitivity analyses of first admissions alone were consistent with the primary analysis.…”
Section: Discussionmentioning
confidence: 59%
“…32 Published literature indicates that outside of outbreaks, only a fraction of ESBL-E identified on wards is transmitted between patients. 24,28,33 Similar results for prevalence on admission and new acquisitions indicate no systematic differences between the intervention periods. Patients readmitted to the wards might have had complex courses of treatment, and thus selection could have had a large role in this group of patients, but the results of sensitivity analyses of first admissions alone were consistent with the primary analysis.…”
Section: Discussionmentioning
confidence: 59%
“…In a previous prospective cohort Dutch study, in which surveillance cultures were taken from contact patients when an MDRO was identified in the index patient roommate, no nosocomial transmission was documented using whole genome sequencing (WGS). 12 Finally, Tschudin-Sutter and colleagues found a remarkably low ESBL-E transmission rate (1.5%) from non-isolated index patients to roommates, with a mean contact period of 4.4 days in a large study performed in a Swiss university hospital. They concluded that nosocomial ESBL-E transmission rates were low when a high level of standard hygiene precautions was applied and that the community reservoir may be an important driver of the emergence and spread of ESBL-E, with an emphasis on the food chain.…”
mentioning
confidence: 97%
“… 2 In addition to the MDR-GNB-colonized patients found during active surveillance studies, MDR bacteria are also unexpectedly found in clinical cultures. 12 …”
mentioning
confidence: 99%
“…2 In addition to the MDR-GNB-colonized patients found during active surveillance studies, MDR bacteria are also unexpectedly found in clinical cultures. 12 The published literature shows a difference in the transmission risk of ESBL-E, suggesting that CPs may not be necessary for all ESBL-positive organisms. Colonization with this kind of organisms usually persists during hospitalization and often for months following discharge.…”
mentioning
confidence: 99%